Comparison of select data mining tools in terms of implementation of association rules discovery - Lízler, Robert (2014)
This bachelor thesis deals with a comparison between two selected data mining software tools, LISp-Miner, developed at the department of information and knowledge engineering at the faculty of informatics and statistics of the University of Economics, Prague, and Rapidminer, a globally popular software suite. The focus of the comparison is mining for association rules. The aim of this work is first to provide a user-oriented evaluation of how the software tools compare in the selected area and second to attempt to discover some interesting differences between the results of how the software tools implement association mining procedures. To reach these goals, the software tools will be tested and evaluated by the author according to a selected set of criteria, grouped into 3 categories: functionality, usability and performance. The work is structured as follows: chapter 1 sets out some theoretical background and introduces the software tools, chapter 2 evaluates the available functionality of the tools for various steps of the overall association mining procedure, chapter 3 rates the software tools based on their usability and user-friendliness, while chapter 4 summarises the results of testing the software tools on a selected data set.